2007
DOI: 10.1159/000104141
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Bone Mass in Postmenopausal Hypertensive Women

Abstract: Background: Ghrelin, a recently discovered peptide mainly secreted by the stomach, has an orexigenic effect which stimulates secretion of the growth hormone. It also has vasodilator effects which reduce blood pressure and stimulate in vitro, bone formation. Objectives: To evaluate the effect of ghrelin on bone mass and bone remodeling markers in postmenopausal hypertensive women. Material and Methods: 25 postmenopausal hypertensive women, light to moderate based on the JNC-VII criteria, were studied. They had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…It also showed a significant decrease in subjects with low BMD versus those with normal BMD. These results are in accordance with those of Pérez-Castrillón et al [6] who reported diminished levels of ghrelin in osteoporotic postmenopausal women. In the latter study, when the patients were separated according to ghrelin tertiles, a greater bone mass was observed in the upper tertiles, which was associated with a decrease in the urinary deoxypiridinoline [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It also showed a significant decrease in subjects with low BMD versus those with normal BMD. These results are in accordance with those of Pérez-Castrillón et al [6] who reported diminished levels of ghrelin in osteoporotic postmenopausal women. In the latter study, when the patients were separated according to ghrelin tertiles, a greater bone mass was observed in the upper tertiles, which was associated with a decrease in the urinary deoxypiridinoline [6].…”
Section: Discussionsupporting
confidence: 93%
“…A positive association between ghrelin and BMD was also reported by Pérez-Castrillñn et al [6] in a study on postmenopausal women. Misra et al [12] found a direct relation between total ghrelin and ghrelin secretion with bone mass measured in the spine and the hip in healthy adolescents.…”
Section: Discussionsupporting
confidence: 78%
“…A study carried out by Turhan et al [44] has shown that six-month administration of isoflavones (59.6 mg genistein with 15.6 mg daidzein) to postmenopausal women led to a significant increase in BMD in the lumbar spine and a concurrent reduction in the biochemical markers of bone resorption. Similar conclusions were obtained by Lee et al [45], who examined the effects of isoflavone supplementation on bone biomarkers in 87 postmenopausal women.…”
Section: Isoflavones and Osteoporosismentioning
confidence: 99%
“…Serum ghrelin is positively correlated with femoral neck BMD in elderly men [62]. However, other observational studies have failed to demonstrate a relationship between ghrelin and BMD in adolescent boys, middleaged, and older adults [63][64][65][66][67]. Treatment of older adults with an oral ghrelin mimetic for 12 months was associated with a small increase in femoral neck BMD, but had no effect on spine or total hip measurements [68].…”
Section: Ghrelinmentioning
confidence: 99%